Early indicators to C4 plant consumption in central Kazakhstan during the Final Bronze Age and Early Iron Age based on stable isotope analysis of human and animal bone collagen - Ananyevskaya, E.; Aytqaly, A. K.; Beisenov, A. Z.; Dmitriev, E. A.; Garbaras, A.; Kukushkin, I. A.; Loman, V. G.; Sapolaite, J.; Usmanova, E.R.; Varfolomeev, V. V.; Voyakin, D. A.; Zhuniskhanov, A. S.; et al. (Elsevier Ltd, 2018)
In this paper, we present new stable isotope data from central, southern and eastern Kazakhstan (KZ) that date to the Early Iron Age. Our primary data together with results from previously published studies demonstrate that the consumption of C4 plants, possibly millet, started in the Final Bronze Age in central KZ and continued into the Early Iron Age. Data from southern KZ, however, demonstrate that over half the human population consumed C4 crops in the Early Iron Age as opposed to the central regions of KZ, where just a few individuals within the population, often males buried in elite kurgans, have high δ13C values indicative of C4 plant consumption. In this paper we aim first to understand if any dietary changes can be seen in the central KZ population during the transitional period between the Bronze and Iron Ages; secondly, we investigate the extent of C4 plant consumption in central KZ during these time periods. Here we present new human isotopic data from nine central sites of the Tasmola culture (n =11), two eastern KZ sites (n =3) and two southern KZ sites (n =26).
Keywords: Stable isotope analysis; Kazakhstan; Early Iron Age; Final Bronze Age; Agriculture; C4 plants; Millet